Analisis Sanksi Hukum Terhadap Produk Minuman Yang Tidak Mencantumkan Logo Halal di Lhokseumawe Berdasarkan Qanun No. 8 Tahun 2016 ( Studi kasus pada MPU Kota Lhokseumawe) - Oka Febriansyah; Fatahillah F; Arif Rahman (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
All products circulating in Aceh are required to have halal certification, as regulated by Qanun No. 8 of the year 2016. Article 34 stipulates that business operators are obligated to apply for halal certification for their products. However, in reality, not all business operators or SMEs (Small and Medium Enterprises) possess halal certification. Therefore, the aim of this research is to address the issue of how sanctions are imposed on products that do not have halal certification, yet are produced or circulated in the city of Lhokseumawe. This research employs a qualitative research method with an empirical approach, focusing on field research and presented in a descriptive manner to depict the issues and existing facts. Sanctions will not be imposed on products lacking halal certification if violations occur among business operators. The reason for not imposing sanctions is the expectation that these business operators and SMEs can contribute to the economic recovery and enhancement of the community's income in the city of Lhokseumawe. Additionally, factors such as limited public awareness and financial constraints hinder the implementation of the regulations stated in Qanun No. 8 of the year 2016.